The Relationship Between Quality Of Work Life And Turnover Intention Of Primary Health Care Physician In Saudi Arabia 2024 (The Review of Diabetic Studies, 2024)
Background: Physician and other health professionals' devotion has been found to be influenced by QWL. There is, however, a dearth of trustworthy data regarding primary health care (PHC) physician ' QWL and desire to leave. The purpose of this study was to investigate the connection between Saudi Arabian PHC physician ' turnover intention and QWL.Methods : In this study, a cross-sectional survey was employed. The Anticipated Turnover Scale, demographic questionnaires, and Brooks' Quality of Work Life survey were used to gather data. The questionnaire was filled out by 300 PHC physician   in the Jazan Region of Saudi Arabia (RR = 87%). ANOVA, t-test, descriptive statistics, General Linear Model (GLM) univariate analysis, standard multiple regression.Results: Nearly 40% of the respondents indicated that they intended to leave their present PHC centers, indicating that they were not happy with their work lives. QWL has a substantial relationship with turnover intention. QWL accounted for 26% of the variance in turnover intention using standard multiple regression, p < 0.001, with R 2 =.263. Conclusions: It is crucial to establish and preserve a pleasant work environment for PHC physician  in order to increase their job satisfaction, lower attrition, boost output, and improve physician  care results.